Acceptability of dietary or nutritional supplementation in pregnancy (ADONS) – Exploring the consumer's perspective on introducing creatine monohydrate as a pregnancy supplement. (March 2020) - de Guingand, Deborah L; Palmer, Kirsten R; Bilardi, Jade E; Ellery, Stacey J
Abstract: Background: Pre-clinical studies suggest maternal dietary creatine supplementation during pregnancy could protect babies against hypoxic intrapartum events, however creatine has not been used as a supplement in pregnancy. The aim of this study was to explore pregnant women and healthcare professional's general knowledge, behaviours, and attitudes toward nutritional supplements, and their thoughts on introducing creatine as a pregnancy supplement. Methods: Pregnant women ( n = 42) and partners ( n = 23), attending a tertiary care pregnancy service in Melbourne, Australia, participated in focus groups or semi-structured interviews. Health professionals ( n = 100), completed a semi-structured online survey. Descriptive data were analyzed using SPSS 25.0 and qualitative data was managed using NVivo 22.0. Results: Use of branded nutritional supplements in pregnancy was commonplace and acceptable. All primary healthcare respondents discussed supplements with their patients at first consultation. Supplements consumed corresponded closely to those recommended. Women had good general awareness of commonly recommended nutritional supplements, however, were less aware of the rationale for supplement use. This aligned with health professional's perceptions. Women would consider taking creatine if recommended by their health professional. Health professionals would require detailed safety, beneficence, and efficacy information before recommending creatine supplementation. They would also be more likely to recommend a new supplement in higher-risk pregnancies, where benefits may outweigh any perceived side-effects. Conclusion: There is high acceptance of current recommended nutritional supplements in pregnancy. Implementing creatine as a new supplement will require substantive empirical evidence and changes to clinical guidelines. Public awareness and education would also be essential to consumer acceptability of creatine.